OSTRACODOS DEL OLIGOCENO DEL SUDESTE DEL LAGO CARDIEL, SANTA CRUZ, ARGENTINA (Ameghiniana, 2013)
Ostracodes from the Centinela Formation from the SE of Cardiel Lake are described. Twenty three genera and 30 species were studied. Eleven taxa were previously identified from the same basin. Two species are doubtfully clasified and 1 taxon could not be identified. Aurila magallanica Kielbowicz 1988 and Australicythere sp.l are the most abundant species. All the ostracodes are moderate or strongly calcified and most of them are omamented, medium in size and with anfidont hinge type. The microfauna suggests a shellow sea, rich in plants, with variable salinity, similar temperature o somewhat higher than that of today at the same latitude, moderate high energy leves and relatively rapid sedimentation. The ostracodes are assigned to the Oligocene according to the results of the Foraminifera study.